2018
DOI: 10.1016/j.ijvsm.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bull spermatozoa during and after cryopreservation: Structural and ultrastructural insights

Abstract: Semen cryopreservation is a well-established procedure used in veterinary assisted reproduction technology applications. We investigated damaging effects of cryopreservation on the structural and ultrastructural characteristics of bull sperm induced at different temperatures and steps during standard cryopreservation procedure using transmission (TEM) and scanning electron microscopy. We also examined the effect of cryopreservation on sperm DNA and chromatin integrity. Five healthy, fertile Friesian bulls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 40 publications
(43 reference statements)
9
101
0
2
Order By: Relevance
“…Furthermore, at the beginning of the incubation, we found that the spermatozoa lacking the acrosome showed the same PTP distribution than those with intact acrosome, while after three hours~80% of the former ones lost the PTP in the head (Table 3, Figure 3). Our basal level of AE detected after thawing and at time 0 could be a consequence of the freezing/thawing process as it is known to cause acrosome loss [46]. Nevertheless, it is known that ejaculated semen has also a fraction of spermatozoa that have undergone AE, which could be another explanation for this initial levels of AE [47].…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, at the beginning of the incubation, we found that the spermatozoa lacking the acrosome showed the same PTP distribution than those with intact acrosome, while after three hours~80% of the former ones lost the PTP in the head (Table 3, Figure 3). Our basal level of AE detected after thawing and at time 0 could be a consequence of the freezing/thawing process as it is known to cause acrosome loss [46]. Nevertheless, it is known that ejaculated semen has also a fraction of spermatozoa that have undergone AE, which could be another explanation for this initial levels of AE [47].…”
Section: Discussionmentioning
confidence: 67%
“…Throughout the freezing and thawing process, spermatozoa are subjected to thermal, osmotic and oxidative stresses that result in alterations in the plasma membrane, reducing their functionality and compromising the results of fertilization (Beran et al, ; Sieme, Oldenhof, & Wolkers, ). During bovine sperm cryopreservation, the plasma membrane is the most affected structure because it may suffer from severe swelling or complete loss (Khalil, El‐Harairy, Zeidan, Hassan, & Mohey‐Elsaeed, ). Bovine spermatozoa also undergo premature capacitation, where they exhibit elevated metabolic rates and an increased membrane fluidity and permeability (Cormier, Sirard, & Bailey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm abnormality is a form of physical defect mostly on the spermatozoa cell body. A primary abnormality is a form of defection on the sperm cell head and acrosome cap, while secondary abnormality is a form of defection mostly on the tail part of the sperm cell [2,19]. This research focused mainly on secondary abnormality which was mostly occurred during frozen semen production.…”
Section: Sperm Abnormalitymentioning
confidence: 99%
“…These results of abnormality percentage of sperm on T1 dan T2 were also still on the range of normal standard of sperm abnormality percentage. Sperm abnormality percentage must be less than 10% in orfer to get a moderate quality of frozen semen [19]. Vitamin E addition with too much low or high level would instead increase sperm abnormality percentage above normal standard.…”
Section: Sperm Abnormalitymentioning
confidence: 99%